Divide and Inform: Rationing Information to Facilitate Persuasion - Michaeli, Beatrice (The Accounting Review, 2017)
ABSTRACT This paper develops a Bayesian persuasion model that examines a manager's incentives to gather information when the manager can disseminate this information selectively to interested parties (“users”) and when the objectives of the manager and the users are not perfectly aligned. The model predicts that if the manager can choose the subset of users to receive the information, then the manager may gather more precise information. The paper identifies conditions under which a regime that allows managers to grant access to information selectively maximizes aggregate information. Strikingly, this happens when the objectives of managers and users are sufficiently misaligned. This finding is robust to variations of the model, such as information acquisition cost, unobservable precision, sequential noisy actions taken by the users, and delayed choice of the subset of users in “the know.” These results call into doubt the common belief that forcing managers to provide unrestricted access to information to all potential users is always beneficial.